Incidence of pneumonitis with CTLA-4 inhibitors in non-small cell lung cancer: a systematic review and meta-analysis - Li, Wei; Xiong, Hao; Peng, Haiying; Yang, Ting; Fan, Li; Zhang, Yanlin (Frontiers in Medicine, 2025)
BackgroundCTLA-4 inhibitors, such as tremelimumab and ipilimumab, are increasingly used in the treatment of non-small cell lung cancer (NSCLC). This meta-analysis aims to evaluate the incidence of pneumonitis associated with these inhibitors and explore potential differences between individual agents.MethodsA systematic search across three online databases identified 911 records. After screening for duplicates and irrelevant articles, nine studies with a total of 4,164 patients were included. Risk of bias was assessed using the Cochrane “Risk of Bias” tool. Pneumonitis incidence was analyzed using a random-effects model.ResultsThe overall incidence of any-grade pneumonitis was 4.0% [95% CI (2.2%, 5.8%)]. High-grade pneumonitis occurred in 1.6% [95% CI (0.5%, 2.6%)]. Subgroup analysis revealed that tremelimumab was associated with a higher incidence of both any-grade (8.0% vs. 2.0%) and high-grade (3.0% vs. 1.0%) pneumonitis compared to ipilimumab. In a comparison with a control group, patients receiving CTLA-4 inhibitors had a significantly higher incidence of any-grade pneumonitis [OR = 3.00, 95% CI (1.60, 5.64), p < 0.01]. However, the difference in high-grade pneumonitis between the two groups was not statistically significant [RR = 1.79, 95% CI (0.83, 3.85), p = 0.14].ConclusionThis meta-analysis indicates that CTLA-4 inhibitors are associated with a higher incidence of pneumonitis in NSCLC patients, particularly with tremelimumab. These findings underline the importance of close monitoring for pneumonitis in patients receiving CTLA-4 inhibitors, especially tremelimumab, and suggest the need for further research into prevention and management strategies.